THE WAY IN WHICH A FINANCIAL STRATEGY CAN CONTRIBUTE TO STRENGTHENING A COMPANY’S SYSTEM OF CORPORATE GOVERNANCE - Kholikova , Rukhsora Sanjarovna; Izzatulloev , Bakhodir Ubaydullo ugli (Educational Research in Universal Sciences, 2023)
In recent years, as a result of extensive reforms implemented in our country, a healthy competitive environment has been formed and the number of competitive companies has been increasing year by year, positively influencing the volume of gross domestic production. In addition to this, the financial and corporate management system of companies located in our country has been growing year by year, attracting foreign and local investments in the leading economic sectors of our country. This article discusses the importance and role of corporate management in companies through their financial strategies.